Pengembangan Lagu Anak-Anak untuk Belajar Matematika Kelas III dengan Tema Perkalian dan Pembagian SDN 04 Masbagik - Hafiz, Alwan; Irawan, Helmi Hendra; Markarma, Muh Ridwan; Muttaqin, Zainul (TAMUMATRA, 2021)
The purpose of this study was to find out how to develop children's songs for learning mathematics in grade III with the theme of multiplication and division in elementary school. This research uses a research and development approach. The types of data in this study are qualitative data and quantitative data. The instrument in this study consisted of a validation sheet and a response questionnaire from students to the use of math songs. The data analysis technique is the data from this research in the form of the expert team's response to the quality of the product developed in terms of the material and instrument aspects used as well as student learning test data in the learning process using math songs. Data in the form of expert response scores were collected through validation sheets, analyzed descriptively with categorization techniques and concluded as input for revising the developed product. While the data in the form of student learning outcomes tests were analyzed using an existing formula. Based on the results of research and discussion, it can be concluded that the development of children's songs for learning mathematics has succeeded in producing a product with the title of multiplication and division